Factors affecting medication assisted treatment success for opioid use disorder. (30th September 2020) - DeLellis, N; Mitchell, M; Frederick, A; Schachman, K
Abstract: Background: In the United States (US) when opioid use disorder (OUD) is treated with medication assisted treatment (MAT), many patients in MAT will relapse into active opioid use during the recovery process. About 23% drop out of treatment within 3 months, and 40-50% drop out within 6 months of MAT start. Using the Anderson and Newman (2005) Framework for Health Services Utilization, 27 variables reflecting predisposing, enabling, and need factors were used to examine the impact on the number of days patients were retained in treatment. Methods: One MAT clinic in rural Michigan used random sample of archival records (n = 390) OUD patients (DSM-V-TR code 304.00, ICD-10 code F11.20) between Jan. 1, 2014 and Nov. 21, 2018 with prescribed buprenorphine as part of MAT program. The first set of linear regressions (backward elimination) defined significant variables for each factor, and the final model included significant variables to predict length of retention in MAT. Results: The first step identified legal issues (predisposing), MSHN insurance, distance to clinic, ability to drive, mental health diagnosis, and homelessness (enabling factors); Zung self-reporting depression score, starting dose, past suicide attempt, Hep-C status, and method of use (needs factor) as statistically significant to be used in the final model, controlling for age and gender. Starting dose (unstandardized b = 136.8, 95%CI 98.0, 175.6), driving license (b = 68.3, CI 13.2, 123.4), distance to clinic (b=-1.1, CI -2.2, -0.5) had statistical impact on the length of stay in MAT. Discussion: This case study identified enabling factors (starting dose and access to clinic) affecting length of participation in MAT. Other factors warranting provider attention were identified for rural OUD patients. Conclusions: Evidence based guidelines for starting doses are needed to increase MAT effectiveness. MAT services should consider distance to clinic as a factor of successful treatment. Key messages: Evidence based guidelines for starting doses are needed to increase MAT effectiveness. Opiood treatment services should consider distance to clinic as a factor of successful treatment.